Hygroscopic properties following drying affects wood consumption by Odontotermes obesus - Ahmed, Sohail; Abbas Naqvi, Syed Khawar; Akbar Sherazi, Ali; Hassan, Babar; Asam Riaz, Muhammad; Zeeshan Majeed, Muhammad (Maderas. Ciencia y Tecnología, 2016)
The relationship between drying and hygroscopic ability of Crateva adansonii and Populus deltoides woods to resist feeding by Odontotermes obesus was studied. Woods were dried under the sun and in the oven for a range of 5-25 days and then these were exposed to termites for 25 days in underground pits in Randomized Complete Block Design pattern with five replications. Results showed that lowest moisture gain was observed at a short time for drying with each method. Weight loss after termites’ exposure was more in less dried sap and heartwood of either plant species. The practical implication of these results is discussed.